Inspired by movenpick jewellery box / Ahmad Fikri Hakimi Ahmad Ghazali - Ahmad Ghazali, Ahmad Fikri Hakimi (2022)
Jewellery box is a box that used to keep your luxury items. This jewellery box are fully inspired by Movenpick Hotel making it outstanding to other shaped.